2018
DOI: 10.1177/0003489418806914
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Treating Early Glottic Neoplasms With a Potassium Titanyl Phosphate Laser

Abstract: The aim of this study was to assess the outcome of treating glottic dysplasia and early squamous cell carcinoma (SCC) with potassium titanyl phosphate (KTP) photoangiolytic laser ablation. Methods: Patient demographics, comorbidities, and tumor characteristics were recorded. Perceptual, patient-reported, and objective voice outcomes were assessed. Use of treatment modalities in addition to the KTP laser, development of locoregional or metastatic SCC, and overall survival were recorded. Results: There were 23 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
1
4
2
Order By: Relevance
“…Laryngeal preservation remained 100% in the non-KTP salvage subgroup. Our KTP re-treatment rate (27%) compares favorably to Nouraei et al 25 While a majority of this subpopulation only required one re-treatment to achieve local control, this concept of the potential need for re-treatment is important to disclose during preoperative counseling. Furthermore, the need for close postoperative observation is paramount to early identification of new glottic pathology and subsequent re-treatment, so patients who have difficulty traveling or may be poor follow-up candidates are perhaps not well-suited for TLM-KTP.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Laryngeal preservation remained 100% in the non-KTP salvage subgroup. Our KTP re-treatment rate (27%) compares favorably to Nouraei et al 25 While a majority of this subpopulation only required one re-treatment to achieve local control, this concept of the potential need for re-treatment is important to disclose during preoperative counseling. Furthermore, the need for close postoperative observation is paramount to early identification of new glottic pathology and subsequent re-treatment, so patients who have difficulty traveling or may be poor follow-up candidates are perhaps not well-suited for TLM-KTP.…”
Section: Discussionsupporting
confidence: 51%
“…To our knowledge, only one study to date 25 has in-depth reporting of re-treatments with the KTP in the OR or office after initial primary TLM-KTP. In that study by Nourei et al, 15 patients with previously untreated T1 or T2 EGC were treated initially by one or two-stage TLM-KTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only independent risk factor for KTP treatment failure was a difficult direct laryngoscopy. They further highlighted that the laryngeal preservation in patients who received KTP was 100%, 31 which is in line with the 97.5% laryngeal preservation rate for early-stage glottic malignancy and carcinoma in situ with RT. Similarly, Zeitels et al reported a 99% and 89% larynx preservation and survival in patients treated with KTP for T1 and T2 disease, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…The final meta-analysis included eight studies (Figure 1). 6,[27][28][29][30][31][32][33] A total of 342 patients underwent KTP laser ablation within the included studies. All the included studies were performed between 2013 and 2022.…”
Section: Search Results and Characteristics Of Included Studiesmentioning
confidence: 99%